Assessing 'Goodness': A Review of Quality Frameworks for Australian Academic Libraries. Issue 3 (3rd July 2017) - Sputore, Alissa; Fitzgibbons, Megan
Abstract: Quality assessment can help a library link its services and performance to strategic university goals and priorities. A vast body of professional literature describes quality and assessment theory and practice in libraries, including comprehensive International Standards. However there is no single measure of 'goodness' for libraries, and choices must be made to ensure assessment activities are effective and sustainable. Libraries seeking to strategically demonstrate their value and proactively respond to emerging priorities have much to gain from an understanding of this field. This review article aims to highlight the features, advantages and outcomes associated with contemporary approaches to quality management and assessment, and offer sources for further exploration. International Standards are discussed, as well as specific methodologies and approaches. This review is placed in the context of current issues and opportunities for Australian academic libraries. Implications for practice A complex range of drivers in the international higher education sector are compelling academic libraries to demonstrate their quality, value and impact. Qualitative and quantitative assessment methods can be used to effectively collect evidence of the quality, value and impact of the library. A range of internationally recognised frameworks can help libraries to take a holistic approach to quality assessment. At a more targeted level, there are a wide range of relevant approaches to assessment that have been successfully used by libraries, and libraries must be strategic in their selection of methods in order to achieve the desired outcomes. An essential outcome from assessing quality must be communicating quality to clients and stakeholders, ideally in the context of broader and strategic institutional goals.